Material Synthesis and Device Aspects of Monolayer Tungsten Diselenide - Yao, Zihan (Sci Rep, 2018)
In this paper, we investigate the synthesis of WSe(2) by chemical vapor deposition and study the current transport and device scaling of monolayer WSe(2). We found that the device characteristics of the back-gated WSe(2) transistors with thick oxides are very sensitive to the applied drain bias, especially for transistors in the sub-micrometer regime. The threshold voltage, subthreshold swing, and extracted field-effect mobility vary with the applied drain bias. The output characteristics in the long-channel transistors show ohmic-like behavior, while that in the short-channel transistors show Schottky-like behavior. Our investigation reveals that these phenomena are caused by the drain-induced barrier lowering (short-channel effect). For back-gated WSe(2) transistors with 280 nm oxide, the short-channel effect appears when the channel length is shorter than 0.4 µm. This extremely long electrostatic scaling length is due to the thick back-gate oxides. In addition, we also found that the hydrogen flow rate and the amount of WO(3) precursor play an important role in the morphology of the WSe(2). The hole mobility of the monolayer WSe(2) is limited by Columbic scattering below 250 K, while it is limited by phonon scattering above 250 K. These findings are very important for the synthesis of WSe(2) and accurate characterization of the electronic devices based on 2D materials.